Transformational leadership, knowledge management, entrepreneurial orientation and organisational excellence in the higher education institutions in Nigeria - Sadiq, Mohammed Abubakar (2014)
The past three decades had witnessed increasing challenge to the higher education institutions especially the public-owned ones. This challenge had been for the institutions to think like the corporate enterprises towards becoming world class so as to ensure improved excellent performances. However, there had been little research on the impact of transformational leadership and knowledge management as well as the moderating role of entrepreneurial orientation on performance excellence of higher education institutions especially in Nigeria. Based on the Resource Based View and Complementary Asset Theory, this study thereby aimed to determine the significance of relationship between transformational leadership and organisational excellence, and the significance of relationship between knowledge management and organisational excellence in the public higher education institutions in Nigeria. The study further aimed to determine the moderating role of entrepreneurial orientation on the relationship between transformational leadership and organisational excellence, and on the relationship between knowledge management and organisational excellence. Data were collected from division heads in the public higher education institutions in the North-Central and South-Western geo-political zones of Nigeria. The study employed multistage sampling procedure with the use of survey questionnaires. Out of the 480 questionnaires distributed, 383 were returned with only 372 usable giving a 77.5 percent response rate. The 372 usable responses were analyzed through SPSS 20.0. Multiple regressions were used to investigate the relationships between transformational leadership, knowledge management, entrepreneurial orientation and organisational excellence. Results showed significant positive relationships between transformational leadership and organisational excellence and between knowledge management and organisational excellence. The results also showed that entrepreneurial orientation moderates the relationship between transformational leadership and organisational excellence, and that of knowledge management and organisational excellence.